CONTEMPORARY ISLAMIC THOUGHT PARADIGM IN UNDERSTANDING TURÂTH AND MODERNITY - Abdul Mukti Ro’uf (Jurnal Ushuluddin, 2018)
This article describes the current map of contemporary Islamic thought in term of understanding the relation between legacy (turâth) and modernity within the context of Arab-Islamic renaissance. Some paradigms of thoughts raised by various critical Arab thinkers converge into one general goal: reviving Arab-Islam civilization from its long hibernation. The theme of “self-criticism” (an-naqd al-dhâtiy) has become a core issue that dominates the discourse of contemporary Islamic thoughts and encompasses other paradigms such as Marxism, liberalism, fundamentalism, nasionalism and post-traditionalism. Although they have a common goal, they have distinctive methods in reading and treating the relation between legacy and modern